Prolapsed bladder following rupture of patent urachal cyst, mimicking bladder exstrophy: a case report and literature review - Kasemsri Srisupundit (2018)
© 2018 The Japan Society of Ultrasonics in Medicine A 26-year-old pregnant woman was diagnosed with fetal bladder prolapse following rupture of a patent urachus/urachal cyst, based on the finding of cyst disappearance with replacement with an infra-umbilical, extra-abdominal solid soft-tissue mass, mimicking bladder exstrophy. The neonatal findings confirmed the prenatal diagnosis. The baby was healthy and had a successful surgical correction. This report provides clues to differentiating ruptured bladder prolapse from bladder exstrophy as follows: (1) well-documented urachal cyst with urine-filled mass in the early gestation, (2) development of solid soft-tissue mass shortly after disappearance of the urachal cyst, and (3) no other structural abnormalities (bladder exstrophy is usually associated with abnormal genitalia, epispadias, or pubic diastasis). This study underlines the differentiation between the two entities because of the vast difference in prognosis, management, and proper counseling.